Seleksi 4 Isolat Terpilih Calon Bibit Sebar G5 Jamur Merang (Volvariella volvaceae) dengan Lama Pengomposan Lima Hari di Majalaya - Montella, Lyra; Lestari, Ani; Bayfurqon, Fawzy Muhammad (UNIVERSITAS LABUHANBATU, 2024)
One of the key factors for successful oyster mushroom cultivation is the use of superior spawn. However, mushroom farmers in the Karawang region face challenges in obtaining affordable and high-quality spawn. To address this issue, efforts have been made to provide superior spawn to oyster mushroom cultivators in Karawang. In a study conducted in Karawang, researchers crossed two parental strains of oyster mushrooms: one from Cilamaya Kulon (white oyster mushroom) and the other semi-wild strain from Purwasari. This crossbreeding resulted in several candidate spawn isolates (G5 Faperta Unsika) with desirable traits inherited from both parent strains. The goal was to identify the best-performing isolate for spawn production. The research was carried out in a 6.5 m x 4 m mushroom house in Dusun Pasir Buah, Desa Pasir Mulya, Kecamatan Majalaya, Kabupaten Karawang. Over a period of 2 months (from April to May 2024), six different spawn isolates were compared: A (G5 FP Semi), B (G5 FP Putih), C (G5 FP001), D (G5 FP010), E (G5 FP024), and F (G5 FP039). Each treatment was replicated five times. The results showed that treatment B (G5 FP Putih) performed the best, with an average harvest weight per tray of 1237.36 g and a total yield of 89.09 kg per mushroom house. Isolate F (G5 FP039) also performed well, with an average harvest weight of 1212.12 g per tray and a yield of 87.27 kg per mushroom house. Therefore, isolate FP039 is recommended as a superior spawn for oyster mushroom cultivation in Karawang Keywords: straw mushroom, spreading seeds, G5 Faperta Unsika isolate